Transnational professionals with Filipino origins in Singapore : transforming identities and sense of belonging. - Yew, Maybeline Wan Hui. (2009)
This paper analyses the migration experience of highly skilled Filipino professionals living in Singapore. It examines the elements that constitute the Filipino identity of these professionals and shows how they negotiate their sense of belonging and identity in relation to their experiences in the Singapore and Filipino societies. This paper documents processes of cultural adaptation in a complex, bi-directional, process of interaction between transnational professionals and the host country that reiterate the dialectical relationship between migration, identity and sense of belonging of Filipino professionals. Based on the narratives of eighteen Filipino professionals located in Singapore, this research analyzes the impact of migration on the changing identities and subjectivities of transnational, Filipino professionals in Singapore. It concludes that social networks and familial ties are important factors contributing to the national belonging and psychological attachment of Filipino professionals.